2012
DOI: 10.1017/s1041610212000658
|View full text |Cite
|
Sign up to set email alerts
|

Dementia knowledge and attitudes of the general public in Northern Ireland: an analysis of national survey data

Abstract: This NILT module provides a unique source of data on attitudes to, and knowledge of, dementia. A key strength is that it provides statistically representative data with national level coverage. This information can be used to target public health education policies more effectively and to inform delivery of health and social services. The success of the module leads us to believe that it stands as a blue-print for collecting information on dementia in other social surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 12 publications
6
106
4
4
Order By: Relevance
“…Those that did know someone with dementia had, on average, a greater dementia knowledge than those that did not (p=0.03). Previous studies in a wider adult population have shown that increased contact with dementia resulted in better dementia knowledge (Dowds et al, 2012;McParland et al, 2012;Reid et al, 2015), though these findings are not always consistent (Lundquist & Ready, 2008). It is therefore possible that spending time with a person with dementia as part of an education programme maybe a simple yet effective way to improve knowledge in adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Those that did know someone with dementia had, on average, a greater dementia knowledge than those that did not (p=0.03). Previous studies in a wider adult population have shown that increased contact with dementia resulted in better dementia knowledge (Dowds et al, 2012;McParland et al, 2012;Reid et al, 2015), though these findings are not always consistent (Lundquist & Ready, 2008). It is therefore possible that spending time with a person with dementia as part of an education programme maybe a simple yet effective way to improve knowledge in adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Whilst the majority of questions were derived from established questionnaires (Dieckmann et al, 1988;McParland et al, 2012), the fact that the measure was not specifically developed from the ground up for this sample could influence students' responses, either in wording used, or the questionnaire responses. For example, "I don't know" was not an option for all dementia knowledge questions and therefore they may have guessed the correct answer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nursing staff working within institutional care who have received training typically show more positive attitudes about people living with dementia (e.g., Leung et al, 2013). Where wider surveys of the attitudes of the general public toward dementia have been undertaken (e.g., McParland et al, 2012), results suggest the general public has, at best, a fair to moderate knowledge about dementia, but there are often misconceptions, such as believing dementia to be a normal part of ageing. Research into attitudes toward dementia often tends to focus on specific issues such as screening for dementia (Bond et al, 2010), euthanasia (Williams et al, 2007) or artificial feeding (Bryon, de Casterlé & Gastmans, 2008), rather than on wider issues.…”
Section: Introductionmentioning
confidence: 99%
“…Those who have already developed dementia often experience additional stigmatization. For instance, McParland, Devine, Innes, and Gayle (2012) reported that residents of Northern Ireland have presented deeply stigmatizing attitudes toward individuals with dementia.…”
mentioning
confidence: 99%